STRATEGI REVITALISASI BERBASIS KARAKTERISTIK TATA RUANG PADA BLOK PEMBENTUK RUANG PRAPATAN LIMA BANDUNG (OBJEK KAJIAN: BLOK JALAN A.YANI – JALAN SUNDA – JALAN NARIPAN): STRATEGI REVITALISASI BERBASIS KARAKTERISTIK TATA RUANG PADA BLOK PEMBENTUK RUANG PRAPATAN LIMA BANDUNG (KASUS STUDI: BLOK JALAN A.YANI – JALAN SUNDA – JALAN NARIPAN) - Tesalonika Tjipto; Yohanes Karyadi Kusliansjah (Ide dan Dialog Desain Indonesia (Idealog), 2026)
Abstract : Prapatan Lima Bandung is a strategic intersection formed by the convergence of five major roads, playing a significant role in the city’s urban development. The area has evolved from the era of local Sundanese settlements, through Dutch colonial rule, to the post-independence period marked by the Asia-Africa Conference (AAC), shaping a complex spatial character. The character of the area includes the presence of both heritage and non-heritage buildings within five urban-forming blocks located in a designated cultural heritage district, comprising a variety of active and inactive structures. The site also spans two Sub-District Regions (SWK): Cibeunying and Karees, each oriented towards tourism and trade-services respectively. Currently, the vitality of spaces and buildings in the area is in decline, necessitating a revitalization effort to reactivate spatial functions and quality in a contextual manner. In this effort, the block with the highest potential as a catalyst has been selected—namely, the block bounded by Jalan Naripan, Jalan Sunda, and Jalan A. Yani. This study adopts a morphological approach encompassing building structures, street networks, and land use patterns; a contextual approach grounded in the historical trajectory of the area; and a spatial character approach focusing on corridor activity, scale, and function. This study aims to examine functions that can activate corridor inhabitance and the building articulation that shapes the spatial structure of Prapatan Lima, Bandung. The research produces design guidelines intended to revitalize contextual spatial articulation and support sustainable social and economic activity. Keywords : Revitalization strategy, Street corridor character, Urban form-generating block, Cultural heritage district, Prapatan Lima Bandung